The Administrative of Higher Education for Excellence of Rajapruk University - Booncham, Manasawan; Petchroj, Laddawan (Journal of Humanities and Social Sciences, Rajapruk University, 2020)
The objectives of this research were to study, to compare and to suggest administrative of higher education for excellence of Rajapruk University. The sample was 360 person’s professors and students of Rajapruk University. By using descriptive statistics such as frequency, percentage, mean, and standard deviation Comparative statistics include t-test, One-way ANOVA, LSD and Focus Group. The research results founded that as following: 1) The Administrative of higher education for excellence of Rajapruk University according to the opinions of professors and students. In general, the operation is at a high level. And each aspect was at a high level in all aspects. With the highest average being the maintenance of arts and culture, followed by the production of graduates, the academic services, research, management and quality assurance respectively. 2) The compare administrative of higher education for excellence of Rajapruk University, found that different age there is an opinion on higher education administration towards excellence, Rajapruk University in overall and in different aspects Statistical significance at the level of .05 except for the gender difference. There is no difference in opinions towards the administration of higher education towards excellence of Rajapruk University. 3) Suggestions from research findings graduate production should adjust the student recruitment system must be clear, specify the criteria that match the ability of the students the most and the fundamental adjustment before studying. In research should promote research and creative work to create intellectual property. In academic services should promote academic services to be more systematic and clear. Focus on short-term training for the public. In the maintenance of art and culture should continue to promote cultural preservation and increase diversity. In management and quality assurance, The university should promote communication about quality assurance that can be used in everyday life or added to the courses taught to students.